2015
DOI: 10.1017/s1751731115000129
|View full text |Cite
|
Sign up to set email alerts
|

Sperm volumetric dynamics during in vitro capacitation process in bovine spermatozoa

Abstract: Previous studies have demonstrated that sperm head morphometry can be used as a potential diagnostic tool for detecting biophysical changes associated with sperm viability in bovine spermatozoa. In this study, sperm head morphometry was used to investigate its value as a biophysical marker for detecting volumetric changes in bovine spermatozoa under in vitro capacitating and non-capacitating incubation conditions. To further test this hypotesis, aliquots of pooled, washed bovine sperm were incubated in either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Many studies indicate a relationship between sperm dimensions and fertility in horses (Hidalgo, Rodríguez, Dorado, & Soler, ; Phetudomsinsuk, Sirinarumitr, Laikul, & Pinyopummin, ), in which fertility disorders have been positively correlated with increased sperm head size (Gravance, Liu, Davis, Hughes, & Casey, ). The subject has also been taken up with regard to fertility in pigs (Saravia et al, ), bulls (Garcia‐Herreros & Leal, ) and dogs (Núñez‐Martínez, Moran, & Peña, ). Differences in head size between fertile and infertile males have been detected in various species (Casey, Gravance, Davis, Chabot, & Liu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicate a relationship between sperm dimensions and fertility in horses (Hidalgo, Rodríguez, Dorado, & Soler, ; Phetudomsinsuk, Sirinarumitr, Laikul, & Pinyopummin, ), in which fertility disorders have been positively correlated with increased sperm head size (Gravance, Liu, Davis, Hughes, & Casey, ). The subject has also been taken up with regard to fertility in pigs (Saravia et al, ), bulls (Garcia‐Herreros & Leal, ) and dogs (Núñez‐Martínez, Moran, & Peña, ). Differences in head size between fertile and infertile males have been detected in various species (Casey, Gravance, Davis, Chabot, & Liu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the in vivo condition is considered to be more efficient as one capacitated sperm is enough for the completion of fertilization for each oocyte (Muro et al, 2016), in vitro capacitation medium for mammalian sperm has also been continuously refined through the introduction of several capacitation inducers and modification of procedure with different approach, as compiled in Table 3. (García-Álvarez et al, 2015;García-Herreros and Leal, 2014;Lukoseviciute et al, 2004;Parrish et al, 1988). There is also an observable trend where the consideration of the use of capacitation inducers leads to recreating the physiological environment of the female genital tract (Chaves et al, 2021), using substances that have been identified to modulate sperm capacitation in vivo such as oviductal fluid (OF) (Navarro-Serna et al, 2021), creatine (Umehara et al, 2018), and the involvement of hormones (estrogen and progesterone) (García-Álvarez et al, 2015).…”
Section: Flaws and Improvementsmentioning
confidence: 99%
“…Some authors have explored the morphological response to diluting or washing the sperm sample,105106 to capacitation107 or to cryopreservation 26108109110…”
Section: Assessment Of Sperm Morphometry II – Functional Aspectsmentioning
confidence: 99%
“…reported how boar spermatozoa in the female reproductive tract are selected on the basis of their size and shape, with those with a larger head and longer tail being those reaching the fertilization site. For sperm morphometric changes during capacitation, García-Herreros and Leal107 reported that the induction of in vitro capacitation in bovine spermatozoa modified sperm head morphometry. As capacitated spermatozoa showed a decrease in all sperm head size and shape parameters, the authors concluded that sperm head morphometry is an objective diagnostic tool for sperm assessment during capacitation.…”
Section: Assessment Of Sperm Morphometry II – Functional Aspectsmentioning
confidence: 99%